Pengaruh Nisbah C/N Campuran Limbah Milk Tea dan Molasses Terhadap Jumlah Bakteri Asam Laktat, pH, Perubahan Fisik Warna, dan Aroma pada Probiotik - Abdul Karim; Deden Zamzam Badruzzaman; Wowon Juanda; Yuli Astuti Hidayati (Unpad Press, 2020)
The objective of the research is to identify the effect of various C/N ratio mixed of milk tea waste and molasses on amount of lactic acid bacteria, pH, physical changes color and aroma in probiotics. The material used in this research are milk tea waste and molasses, fermented in anaerobic. The research method uses a Completely Randomized Design (CRD) by 3 treatments, which are P1 = C/N ratio 25, P2 = C/N ratio 30, P3 = C/N ratio35, with 6 repetitions. The measured parameters are amount of lactic acid bacteria, the pH and physical changes color and aroma. The data were analyzed by Analysis of Variance (ANOVA) method based of Tukey Test. The results of this research showed that there is a significant effect (P < 0,05) between a various of C/N ratio on amount of lactic acid bacteria, pH levels and physical changes color and aroma in the results of fermentation (probiotics). The best respond is on the C/N ratio 30, so it can produced high amount of lactic acid bacteria with an average of 2,06 x 109 CFU/mL, an average pH of 3,75 and physical changes in color and aroma.